3D street art illusions: embedding chalk stylized rendering of 3D objects into a pavement photo. (7th October 2014) - Way, Der‐Lor; Hsieh, Cheng‐Han
Abstract: Three dimensional street art illusions have become more popular in recent years. Many of them are drawn on pavement such as streets, sidewalks, and town squares. It is often known as 3D chalk art, where a 2D artwork is drawn on the street, giving the viewer a 3D optical illusion from a certain perspective. This paper supplies chalk stylized renderings for 3D models and synthesizes 3D objects into a realistic photograph. Users can input one photo for the 3D model. First, a camera position is achieved by using a camera calibration algorithm. Second, a chalk stylized rendering was applied to create an artistic image of the 3D models using the same camera position. Then, the non‐photorealistic rendering image is composited into a source photograph using a modified Poisson approach. All of the enhanced pavement texture details are also blended into the object's image. The major contribution of this paper is providing a user to create any interesting and attractive 3D illusionary art without physically drawing pictures on the pavement. Finally, the proposed method is demonstrated using various experimental 3D street art illusion images. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : User inputs a photo and 3D model. First, a user needs to annotate two pairs of parallel lines in the street image. Then, two vanishing points are estimated for recovering the camera's position. The 3D models are rendered using the proposed chalk stylized rendering technique at the same camera position. Finally, the object's non‐photorealistic rendered image is embedded into a street photo by using a modified Poisson blending approach.